Preconception Health and Lifestyle Behaviours of Women Planning a Pregnancy: A Cross-Sectional Study - Chivers, Bonnie R. (J Clin Med, 2020)
Preconception care and lifestyle behaviours significantly influence health outcomes of women and future generations. A cross-sectional survey of Australian women in preconception, stratified by pregnancy planning stage (active planners (currently trying to conceive) vs. non-active planners (pregnancy planned within 1–5 years)), assessed health behaviours and their alignment to preconception care guidelines. Overall, 294 women with a mean (SD) age of 30.7 (4.3) years were recruited and 38.9% were overweight or obese. Approximately half of women (54.4%) reported weight gain within the previous 12 months, of which 69.5% gained ≥ 3kg. The vast majority of women (90.2%) were unaware of reproductive life plans, and 16.8% over the age of 25 had not undertaken cervical screening. Of active planners (n = 121), 47.1% had sought medical/health advice in preparation for pregnancy and 81.0% had commenced supplementation with folic acid, iodine or a preconception multivitamin. High-risk lifestyle behaviours including cigarette smoking (7.3%), consumption of alcohol (85.3%) and excessive alcohol consumption within three months (56.3%), were frequently reported in women who were actively trying to conceive. Results indicate that women who are actively planning a pregnancy require support to optimise health and lifestyle in preparation for pregnancy to improve alignment with current preconception care recommendations.